Pelatihan literasi kewirausahaan berbasis praktik dalam meningkatkan produktivitas Generasi Z - Siti Nur Aisya Putri; Ufi Ulfiah (Nur Science Institute, 2026)
The limited integration between literacy activities and entrepreneurial practice has constrained the development of productivity among Generation Z. Literacy is often confined to reading activities, disconnected from reflection and real-world application, resulting in minimal impact on critical thinking and independence. Therefore, this study aims to enhance Generation Z productivity through a practice-based entrepreneurial literacy training program. The program was conducted from November 22 to December 6, 2025, involving both internal and external university students and the general public. The methods included literacy and entrepreneurship exhibitions, a structured reading practice of one book per week integrated with purchasing student products, and reflective writing activities covering book titles, emotional responses, and self-confidence levels. The results indicate that 171 participants experienced increased productivity and self-confidence, reaching 90–100%. These findings suggest that integrating literacy, self-reflection, and entrepreneurial practice fosters productive learning habits, improves critical thinking, and promotes creativity and independence among students.